2007
DOI: 10.1051/0004-6361:20066918
|View full text |Cite
|
Sign up to set email alerts
|

Low surface brightness galaxies around the HDF-S

Abstract: Aims. With this study we aim at the spectroscopic verification of a photometrically selected sample of Low Surface Brightness (LSB) galaxy candidates in a field around the Hubble Deep Field-South (HDF-S). The sample helps to extend the parameter space for LSB galaxies to lower central surface brightnesses and to provide better estimates on the volume densities of these objects. Methods. To derive redshifts for the LSB candidates, long-slit spectra were obtained covering a spectral range from 3400 Å to 7500 Å. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
1
19
1
1
Order By: Relevance
“…Kolmogorov-Smirnov tests show that the different mean of distributions between LSBGs and HSBGs is 16.0%. The result that LSBGs have lower stellar metallicities is consistent with the lower metallicities of LSBGs found in gas-phase (McGaugh 1994, Galaz et al 2006, Haberzettl et al 2007b. Liang et al (2010) found that the decreasing of metallicities with decreasing surface brightness could be due to the decreasing stellar masses with decreasing surface brightness.…”
Section: Distributions Of Stellar Masses Stellar Metallicities Effesupporting
confidence: 81%
“…Kolmogorov-Smirnov tests show that the different mean of distributions between LSBGs and HSBGs is 16.0%. The result that LSBGs have lower stellar metallicities is consistent with the lower metallicities of LSBGs found in gas-phase (McGaugh 1994, Galaz et al 2006, Haberzettl et al 2007b. Liang et al (2010) found that the decreasing of metallicities with decreasing surface brightness could be due to the decreasing stellar masses with decreasing surface brightness.…”
Section: Distributions Of Stellar Masses Stellar Metallicities Effesupporting
confidence: 81%
“…There are several reasons to suspect that the galaxies at large impact parameters are in fact the host galaxies of these sub‐DLA systems. The ever possible scenario of an LSB galaxy at low impact parameter is unlikely, as the low metallicities of LSB galaxies (McGaugh 1994; Habberzettl, Bowmans & Dettmar 2007) exclude them as possible candidates for these high‐metallicity sub‐DLA systems. The probability of observing any interloping field galaxy with L > L ★ in a pencil beam survey such as this is small, as is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The SDSS, which has provided much of the discovery space for astronomers in the local and intermediate redshift Universe, is incomplete beyond an rband effective surface-brightness of ∼23 mag arcsec −2 (e.g. Driver et al 2005;Blanton et al 2005;Zhong et al 2008;Bakos & Trujillo 2012;Williams et al 2016) since the majority of these objects are much fainter than this limit (Haberzettl et al 2007;Martin et al 2019) bespoke reductions (e.g. Stierwalt et al 2015;Fliri & Trujillo 2016) or purpose built instruments (e.g.…”
Section: Introductionmentioning
confidence: 99%